2014
DOI: 10.1007/s00586-014-3731-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk prediction model for tracheostomy in acute traumatic cervical spinal cord injury patients

Abstract: We suggest using the CART model in clinical applications. Patients with AAMS ≤ 1 exhibit an increased likelihood of requiring a tracheostomy. For patients with an AAMS in the range of 2-22, surgeons should consider giving these patients a tracheostomy once respiratory complications occur. Surgeons should be cautious to give a tracheostomy to patients with an AAMS ≥ 23, if the patient experiences an incomplete spinal cord injury and the HSC in the spinal cord is at C3 level or lower based on MRI. For other pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…It is reported that the tracheostomy rate ranges from 8.4% to 62.1% in patients with CSCI [ 8 – 23 ]. Although many studies have investigated the factors that affect tracheostomy after CSCI, the results are different, and a consensus on the predictive factors for tracheostomy has not yet been reached [ 9 , 24 ]. This study is the first to perform a meta-analysis on various reported factors that influence tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the tracheostomy rate ranges from 8.4% to 62.1% in patients with CSCI [ 8 – 23 ]. Although many studies have investigated the factors that affect tracheostomy after CSCI, the results are different, and a consensus on the predictive factors for tracheostomy has not yet been reached [ 9 , 24 ]. This study is the first to perform a meta-analysis on various reported factors that influence tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…The influencing factors for tracheostomy after CSCI have been widely studied. Among these previous studies, age [ 8 21 ], sex [ 8 , 9 , 11 , 12 , 14 16 , 19 , 20 , 22 ], AIS (American Spinal Injury Association Impairment Scale) [ 8 22 ], neurological level of injury (NLI) [ 8 , 9 , 11 , 12 , 14 , 16 – 23 ], injury seventy score (ISS) [ 8 , 9 , 12 , 14 , 19 , 20 , 22 ], Glasgow Coma Scale (GCS) score [ 8 , 11 , 14 , 15 ], associated injury [ 8 , 9 , 11 , 12 , 16 , 19 ], respiratory complications [ 9 , 10 , 12 , 13 , 19 ], smoking history [ 9 , 16 , 19 , 21 ], and other factors have been reported. However, a consensus has not been reached due to the differences among these previous results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion level, as well as completeness, is important. Changes on magnetic resonance imaging at the C3 level are predictive of the need for tracheostomy [115] and C omo et al [29] found a tracheostomy rate of 81–83% in patients with a complete SCI above the level of C5. Overall tracheostomy incidence in tetraplegia is reported to be between 10% and 60% [116, 117] with FVC being an important predictor of the need for tracheostomy, with cut-points of <830 and ≤500 mL.…”
Section: Respiratory Treatmentmentioning
confidence: 99%
“…As an automatic “machine‐learning” method, classification and regression tree (CART) analysis can be used to classify people into ordinal risk or clinically important categories. This tree‐building technique could help in the selection of risk factors irrespective of their distributions or interactions; it has been shown to be effective in the development of clinical decision rules that perform as well or better than rules developed using more traditional methods . This simple classification tool may also help to provide a reference pattern of risk discrimination for clinical decision‐making on hip fracture prevention.…”
Section: Introductionmentioning
confidence: 99%